2022
DOI: 10.1002/cbin.11764
|View full text |Cite
|
Sign up to set email alerts
|

Paneth cells and their multiple functions

Abstract: The small intestine mucosa is lined by specialized cells that form the crypt-villus axis, which expands its surface. Among the six intestinal epithelial cell types, the Paneth cell is located at the base of the crypt, and it contains numerous granules in its cytoplasm, composed of antimicrobial peptides, such as defensins and lysozyme, and growth factors, such as epidermal growth factor, transforming growth factor-α, and Wnt ligands. Together, these elements act in the defense against microorganisms, regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…Beside their role in the secretion of anti-microbial products, Paneth cells regulate the gut immune homeostasis through secretion of cytokines including IL-17A and TNF-α [2225]. Our analysis of immune cell subsets in the small intestines of wild-type and Sox9 ΔIEC mice showed striking differences in their ILC populations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Beside their role in the secretion of anti-microbial products, Paneth cells regulate the gut immune homeostasis through secretion of cytokines including IL-17A and TNF-α [2225]. Our analysis of immune cell subsets in the small intestines of wild-type and Sox9 ΔIEC mice showed striking differences in their ILC populations.…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that Paneth cells directly sense gut commensals and maintain homeostasis at the intestinal host-microbial interface through production of anti-microbials and cytokines [20,21]. Thus, Paneth cells produce a-defensins, lysozyme, and phospholipase A2, and contribute to immune homeostasis through production of cytokines (TNF-a and IL-17A) [22][23][24][25]. As a main source of anti-microbial products in the gut, Paneth cells are believed to play a protective role in the development of metabolic disorders and obesity [20,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the molecules involved, Paneth cells are the epithelial component of stem cell niche (Beumer & Clevers, 2021) and for maintenance of the intestinal microbiota, and they integrate a highly organized physical and immunological barrier (Barreto E Barreto et al, 2022). Molecular mechanisms leading to changes in secretory Paneth cells have been linked to inflammatory bowel diseases, such as Crohn's disease and necrotizing enterocolitis (Barreto E Barreto et al, 2022). It is evident that the dedifferentiation of Paneth cells is dependent on the constitutive activation of Notch pathway in the intestinal epithelium (Yu et al, 2018), and on its target Hes1.…”
Section: Discussionmentioning
confidence: 99%
“…In the stomach, previous studies reported that EW increases the proliferation and anticipates the maturation of mucous neck and zymogenic cells in the gastric mucosa of rat pups (Ghizoni et al, 2014; Zulian et al, 2017), and part of these effects extend to adulthood (Teles Silva et al, 2020). The intestinal niche in the crypt depends on signaling and on the organization with Paneth cells (Barreto E Barreto et al, 2022). Among the targets of the Wnt pathway, Ascl2 expression is essential for Lgr5+ stem cell maintenance, and its loss is associated with crypt hyperplasia and pouch‐like projections on the villi (van der Flier et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation